PENGARUH KUALITAS PRODUK WISATA, KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PENGUNJUNG OBJEK WISATA GOA KREO SEMARANG - Ananditya, Adrian Dwiki; Hidayat, Wahyu (Jurnal Ilmu Administrasi Bisnis, 2017)
Currently, the development of tourism in Indonesia is growing more rapidly, this is caused in part by the many interesting sights like Goa Kreo in Semarang. However, there is still a lack of visitors rate the quality of tourist products and quality of service that is causing the lack of visitor satisfaction. This study aims to determine the effect of product quality travel service quality and promotion of visitor satisfaction Attractions Goa Kreo Semarang. This type of research is explanatory research, with data collection through questionnaires and interviews. The sampling technique uses accidental sampling method. The sample in this study amounted to 100 respondents who are a visitor attraction Kreo Goa. This study concluded that the quality of tourism products, quality of service and promotion of visitor satisfaction, either partially or simultaneously. service quality variables have the greatest influence of other variables. The results obtained by analyzing primary data using validity, reliability test, cross tabulation, correlation coefficient, simple regression analysis, coefficient of determination, significance test (t test) in both directions. Based on this, the researchers suggested that managers can improve the quality of tourism products back and promotions Attractions Goa Kreo that increased visitor satisfaction.